Biological Importance and Phytochemistry of Neptunia oleracea Lour: A Mini Review - Sonia Devi, Okram; Nabachandra singh, Thoudam; Jairaj Singh, Laishram; Prasanta Singh, Thokchom (Asian Journal of Chemistry, 2021)
Neptunia oleracea is an important medicinal plant used in treating various ailments in different countries. The plant contains chlorophyll-related compounds, amino acids, vitamins, etc. The presence of pheophorbide a and its related compounds make this plant a promising antitumor plant. The plant is used for sewage water treatment and is also utilized in nitrogen fixation in a wetland ecosystem. The present review emphasizes the traditional uses, biological activites and phytochemistry of N. oleracea.